2018
DOI: 10.1534/genetics.118.301617
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain DLC-1 Facilitates the Function of the Germline Cell Fate Regulator GLD-1 in Caenorhabditis elegans

Abstract: Developmental transitions of germ cells are often regulated at the level of post-transcriptional control of gene expression. In the Caenorhabditis elegans germline, stem and progenitor cells exit the proliferative phase and enter meiotic differentiation to form gametes essential for fertility. The RNA binding protein GLD-1 is a cell fate regulator that promotes meiosis and germ cell differentiation during development by binding to and repressing translation of target messenger RNAs. Here, we discovered that so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In mouse models, the mutation or loss of HMMR/Hmmr expression also disrupts the correct development or homeostasis of gonadal tissues [7,50,51]. While the mechanisms responsible are yet to be determined, these phenotypes are likely reflective of the high expression of HMMR in gonadal tissues and the necessary role played by dynein, and its adaptor proteins, during the processes of gametogenesis and spermatogenesis [52][53][54].…”
Section: Hmmr Is Needed For Tissue Homeostasis and Neural Developmentmentioning
confidence: 99%
“…In mouse models, the mutation or loss of HMMR/Hmmr expression also disrupts the correct development or homeostasis of gonadal tissues [7,50,51]. While the mechanisms responsible are yet to be determined, these phenotypes are likely reflective of the high expression of HMMR in gonadal tissues and the necessary role played by dynein, and its adaptor proteins, during the processes of gametogenesis and spermatogenesis [52][53][54].…”
Section: Hmmr Is Needed For Tissue Homeostasis and Neural Developmentmentioning
confidence: 99%
“…It was reported that DLC-1 of C. elegans and Plasmodium falciparum played an important role in growth and germ cell proliferation and gametogenesis in vivo (Daher et al, 2010;Ellenbecker et al, 2019). DLC-1 (Sjp_0057280), which is involved in microtubule-based process/microtubule-associated complex/microtubule cytoskeleton, was also identified as differentially expressed in female schistosomes from SCID mice when compared with those from BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…In GSCs, transcription of the differentiation factor bam is repressed by the BMP signaling pathway FIGURE 5 | Schematic illustrating some components that regulate C. elegans germline development, including the Puf family members FBF-1 and FBF-2. Modeled after Ellenbecker et al (2019). (Chen and McKearin, 2003a,b;Song et al, 2004;Chen and McKearin, 2005).…”
Section: The Regulation Of Drosophila Germ Cell Differentiation By Mrna Translation Based Mechanismsmentioning
confidence: 99%
“… Schematic illustrating some components that regulate C. elegans germline development, including the Puf family members FBF-1 and FBF-2. Modeled after Ellenbecker et al (2019) . …”
Section: Rna Binding Proteins and The Regulated Translation Of Mrnas During Germ Cell Formationmentioning
confidence: 99%